Does timing of alloplastic breast reconstruction in older women impact immediate postoperative complications? An analysis of the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) database. (December 2019) - Angarita, Fernando A.; Dossa, Fahima; Hermann, Naama; McCready, David R.; Cil, Tulin D.
Abstract: Background: Alloplastic breast reconstruction is safe in well-selected older women. The impact of timing of surgery on complication rates is unknown. This study aimed to determine the immediate (30-day) postoperative complication rates of older women who underwent immediate (IBR) and delayed breast reconstruction (DBR) with alloplastic techniques. Methods: The American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) database was used to identify women ≥70 years old with in situ or invasive breast cancer who underwent either IBR or DBR (2005–2016). Outcomes included 30-day postoperative morbidity and mortality. Results: A total of 2, 085 older women underwent alloplastic breast reconstruction of which 90% and 10% were IBR and DBR, respectively. Both groups had similar median age, body mass index, and frequency of smoking, diabetes mellitus, and steroid use. Tumors were mainly invasive in the IBR group (83.5%) and in situ in the DBR group (83.3%). IBR had significantly longer operative times (median 154 min vs 98 min, p < 0.0001), but equal length of stay (median 3 days vs 3 days, p = 0.1). The 30-day overall morbidity (medical or surgical complication) rate was significantly higher in the IBR group (7.5% vs 1.0%, p < 0.0004). Women with IBR were significantly more likely to develop infectious complications (6% vs 1%, p = 0.002). Cardiac/transfusion, pulmonary, thromboembolic, renal, and neurological morbidity rates were equal between groups. Thirty-day mortality rates were similar across both groups (IBR: 0.05% vs DBR: 0%, p = 0.74). Conclusions: While overall thirty-day postoperative complication rates in older women who undergo breast reconstruction were low, there were higher rates of infectious complications in the IBR cohort. The risks and benefits of alloplastic breast reconstruction should be discussed with older women undergoing mastectomy for breast cancer treatment. Highlights: Alloplastic breast reconstruction is safe in well-selected older women. Thirty-day postoperative complication rates are overall low. Alloplastic breast reconstruction should be discussed with older women.